Editorial Comments - Marie Poggenpoel (AOSIS, 2000)
One central theme that appears in all the articles of this edition of Health SA Gesondheid is how crucial positive interpersonal relationships are between all role-players in the health care system. Integral to positive interpersonal relationships are mutual respect, acceptance, empathy, genuiness and clear and constructive communication. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.